Bioinspired photothermal zwitterionic fibrous membrane for high-efficiency solar desalination and electricity generation - Yuzhu Wang; Feng Chen; Qiaochu Chen; Wei Liu; Qihang Huang; Xinru Hou; Shuang Li; Chong Cheng; Xiaodong Xie; Nan Meng; Yaozu Liao (Nature Communications)
Abstract Solar-driven desalination holds great promise for addressing the scarcity of global freshwater. However, salt accumulation remains a significant challenge, particularly for two-dimensional membrane materials. Inspired by aquaporins, we design a porous zwitterionic fibrous membrane that selectively transports water while rejecting Na+ and Cl−, achieving efficient evaporation and salt resistance. The incorporation of porphyrin-based conjugated microporous polymers enhances photothermal conversion and antibacterial properties, while zwitterionic groups and porous structure disrupt high-salinity gradients, effectively preventing salt deposition. The membrane achieves an evaporation rate of 2.64 kg m−2 h−1 and a photothermal efficiency of 97.6% under 1 kW m−2 solar irradiation. Furthermore, the coupling of photothermal evaporator and thermoelectric module achieves a stable electric output (power density: 1.5 W m−2). This work presents a synergistic strategy for salt resistance, water purification and energy generation, advancing the design of solar-thermal-electric integrated systems.